Laudation for Ágnes Herczeg - Őrfi, József (4D Journal of Landscape Architecture and Garden Art, 2012)
I feel like a student taking an exam and facing with the most difficult question. I have to praise Ms. Ágnes Herczeg and I have had a hard time finding proper words for her laudation. Not because she wouldn't deserve it, but because I can hardly find worthy expressions for it.
Keywords: laudation